Identifying the Added Value and Requirements of Telerehabilitation in Home-based Geriatric Rehabilitation: An Exploratory Qualitative Study - Chris J. Gamble; Eleonore van Dam van Isselt; Sandra M.G. Zwakhalen; Noah Adams; Dennis P.H.G. Roekx; Jolanda C.M. van Haastregt (International Journal of Telerehabilitation)
Geriatric rehabilitation (GR) facilities are turning to innovative tools such as telerehabilitation to support home-based treatment due to challenges with population ageing, staff shortages, and mounting budgetary pressures. This study identified the potential added value as well as the requirements of using telerehabilitation in home-based GR, according to stakeholders and potential end-users. This exploratory qualitative study design conducted semi-structured interviews among nineteen care professionals, three patients and one informal caregiver. The qualitative data from these interviews were transcribed verbatim and analysed with inductive content analysis. Interviewees indicated multiple added values and requirements for telerehabilitation in home-based GR. Overall, there was great emphasis on blended care implementation, in which telerehabilitation is used in conjunction with in-person care. It is recommended to use the present findings towards developing and implementing a telerehabilitation intervention in home-based GR and assess its feasibility and usability.